2017
DOI: 10.1038/s41598-017-08668-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional validation of GPIHBP1 and identification of a functional mutation in GPIHBP1 for milk fat traits in dairy cattle

Abstract: In a previous genome-wide association study (GWAS) on milk production traits in a Chinese Holstein population, we revealed that GPIHBP1 is a novel promising candidate gene for milk fat content traits. In this study, we performed over-expression and RNAi experiments on GPIHBP1 in bovine primary mammary epithelial cells. The results showed that the expression of several important milk fat-related genes (LPL, CD36, VLDLR, ACACA and FASN) increased or decreased when the expression of GPIHBP1 was up- or down-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The well-known DGAT1 p.A232K-variant [35] can be excluded as the causal variant for the milk production QTL on BTA14 because it does not segregate in Brown Swiss cattle [11]. For a QTL for milk production traits in close vicinity to DGAT1 on BTA14, the GPIHBP1 gene has been postulated as candidate gene [34,36].…”
Section: Milk Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The well-known DGAT1 p.A232K-variant [35] can be excluded as the causal variant for the milk production QTL on BTA14 because it does not segregate in Brown Swiss cattle [11]. For a QTL for milk production traits in close vicinity to DGAT1 on BTA14, the GPIHBP1 gene has been postulated as candidate gene [34,36].…”
Section: Milk Productionmentioning
confidence: 99%
“…Another two QTL for milk production traits were located on BTA14 and BTA16. Both regions have recently been described to harbor QTL for milk production traits in several cattle breeds including Brown Swiss [11,33,34]. The well-known DGAT1 p.A232K-variant [35] can be excluded as the causal variant for the milk production QTL on BTA14 because it does not segregate in Brown Swiss cattle [11].…”
Section: Milk Productionmentioning
confidence: 99%
“…Another two QTL for milk production traits were located on BTA14 and BTA16. Both regions have recently been described to harbor QTL for milk production traits in several cattle breeds including Brown Swiss [11, 16, 17]. The well-known DGAT1 p.A232K-variant [18] can be excluded as the causal variant for the milk production QTL on BTA14 because it does not segregate in Brown Swiss cattle [11], but mutations in DGAT1 other than the p.A232K-variant might segregate in Brown Swiss.…”
Section: Resultsmentioning
confidence: 99%
“…The unannotated gene is LOC104973964, while the rest are protein-coding genes: LOC112441461, LOC787628, LY6H, GPIHBP1 LY6E, LY6L, GML, and CYP11B1. In previous research, Yang et al (Yang et al, 2017) found the gene GPIHBP1 related to the fat milk trait in dairy cattle. Further investigation of the relationship of the listed genes with the phenotype of interest (beyond the scope of this paper) would be needed.…”
Section: Classification With Decision Treesmentioning
confidence: 99%